Violência e maus tratos contra pessoa idosa: um estudo de representações sociais construídas por jovens, adultos e idosos - Amaral, Ana Karênina de Freitas Jordão do (2017)
Introduction: Violence against elderly is considered a public health problem, both in terms of magnitude and impact: political, social, economic, cultural, capable of negatively influencing quality of life, interfering with a healthy and fulfilling life. It is an important object of research in social and academic prisms and its findings can contribute to adoption of health practices and socially contextualized protective actions, considering psychosocial and cultural dimensions to meet unique needs of specific groups. Objectives: To investigate the theme of Theory of Social Representations and the aging published in articles; Investigate the social representations on violence and ill-treatment against the elderly people built by young people, adults and old people; Identify the types of violence against the elderly, according to the Ecological Model by the participating groups. Method: Exploratory study of mixed approach, with 150 participants, of both sexes, randomly chosen in João Pessoa / Paraíba / Brazil, from March to September / 2015. The empirical data originated from a three-part semi-structured interview: the first was a Free Word Association Test with terms inducing "violence against elderly" and "maltreatment against elderly"; The second corresponds to questions organized from the Ecological Model for understanding violence and the third part with sociodemographic data. The data were organized in two corpus and processed using the software IRaMuTeQ® and the database analyzed by SPSS 20.0. Results and Discussion: This research originated three articles: the first one of bibliometric revision on scientific production of Theory of Social Representations in the context of aging in which it was evidenced more production of authors from Northeast; demonstrating an publications increase in 2011; the second article deals with social representations about violence and abuse against the elderly by young people, adults and the elderly, in which the results point to socio-cognitive content on violence defined from three classes: descriptions of criminal acts; motivations for violence and types of violence; sociocognitive contents for ill-treatment are defined in two classes: vulnerability to ill-treatment and descriptions of family mistreatment. The third study deals with types of violence according to the Ecological Model in which sociodemographic variables were related to risk factors for violence described by the WHO and in which the results indicate a greater understanding of elderly on violence types. Conclusions: Publications investigated in bibliometrics indicate that the dependence of another person on the performance of daily activities interferes in the quality of life, pointing out the SR as important in the identification of the weaknesses / vulnerabilities experienced by the elderly. From the SR found in the groups, it was verified that young people evoked different types of violence, aware that it is not only physical; adults evoked content related to contraventions associated with violence against "frail", "defenseless" elderly; elderly people presented an expanded theme view, since they suffer with lack of love and disrespect after years to the dedication family. The theme of violence is very complex, needs changes in levels of health, criminal justice, social welfare. All the information presented confirms the premises of the EM.